2013
DOI: 10.1002/elan.201200610
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mercury Film Glassy Carbon Electrode Modified with Multiwalled Carbon Nanotubes in Electrochemical Analysis of DNA

Abstract: Mercury film plated on a glassy carbon electrode modified with multiwalled carbon nanotubes (MF/MWNTs/GCE) was used for the analysis of single (ss) and double stranded (ds) DNA, as well as for Jurkat genomic DNAs methylated to different degrees. The results indicated that the DNA molecules adsorbed quite strongly on the MF/MWNTs/GCE surface allowing ex situ adsorption and produce well developed peaks (due to cytosine and adenine) by using adsorptive stripping (Ads, ex situ) square wave voltammetry (SWV). Also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 108 A sandwich-type DNA biosensor based on electrochemical coreduction synthesis of graphene-three-dimensional nanostructure gold nanocomposite films was developed with high sensitivity due to its high active surface area and high conductivity. 109 Other materials such as CHIT–ionic liquid 110 and mercury film/carbon nanotubes 111 as well as biocompatible nanostructured magnesium oxide-CHIT platform 112 were also used as advanced electrode materials to design high performance genosensors.…”
Section: Genosensorsmentioning
confidence: 99%
“… 108 A sandwich-type DNA biosensor based on electrochemical coreduction synthesis of graphene-three-dimensional nanostructure gold nanocomposite films was developed with high sensitivity due to its high active surface area and high conductivity. 109 Other materials such as CHIT–ionic liquid 110 and mercury film/carbon nanotubes 111 as well as biocompatible nanostructured magnesium oxide-CHIT platform 112 were also used as advanced electrode materials to design high performance genosensors.…”
Section: Genosensorsmentioning
confidence: 99%
“…It has been shown that assay performance of nanocarbon-film electrode based strategies are highly relied on the physical properties of the electrodes and their functionalization. More recently, carbon based GCE and screen-printed electrodes have also been successfully modified with conducting polymer, carbon nanotubes, nanocomposite and nanostructured gold materials used to analyze DNA methylation (Wang et al, 2016b;Zhu et al, 2015;Wang et al, 2013;Serpi et al, 2013;Zhu et al, 2015;Daneshpour et al, 2016;He et al, 2011). For example, Daneshpour et al, (2016) chemically modified screen printed carbon electrode surfaces with Fe3O4/N-trimethyl chitosan/gold nanocomposite and polythiophene to quantify 5mC in a RASSF1A tumor suppressor gene.…”
Section: Methylation Assay Using Carbon Based Electrodesmentioning
confidence: 99%